2017
DOI: 10.1021/acs.joc.7b02463
|View full text |Cite
|
Sign up to set email alerts
|

BF3·OEt2-Mediated Tandem Annulation: A Strategy To Construct Functionalized Chromeno- and Pyrano-Fused Pyridines

Abstract: A simple and efficient one-pot annulation of arylidenones, alkynes, and nitriles in the presence of BF·OEt is described. A highly functionalized variety of N-substituted pyridine-fused chromeno and pyrano derivatives were obtained with satisfactory yields under mild reaction conditions. The method was proven to be valid for the synthesis of a diverse library of chromeno[3,4-c]pyridines, thiochromeno[3,4-c]pyridines, pyrano[3,4-c]pyridines, and thiopyrano[3,4-c]pyridine derivatives from readily accessible subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We were also successful in expanding the scope of this reaction towards the synthesis of chromanone/thiochromanone/pyanone/and thiopyranone fused N-acetylated pyridines. 38 Among different types of pyridine molecules 2,4,6-triarylpyridines, which are known by the name of Krohnke pyridines have gained the attention of scientific community owing to its broad applications in multiple fileds. 39 In 2018, Zhang and co-workers accomplished a metal free synthesis of 2,4,6-triaryl pyridines 69 from chalcones 8 and N-unsubstituted enaminones 68 (Scheme 24).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We were also successful in expanding the scope of this reaction towards the synthesis of chromanone/thiochromanone/pyanone/and thiopyranone fused N-acetylated pyridines. 38 Among different types of pyridine molecules 2,4,6-triarylpyridines, which are known by the name of Krohnke pyridines have gained the attention of scientific community owing to its broad applications in multiple fileds. 39 In 2018, Zhang and co-workers accomplished a metal free synthesis of 2,4,6-triaryl pyridines 69 from chalcones 8 and N-unsubstituted enaminones 68 (Scheme 24).…”
Section: Reviewmentioning
confidence: 99%
“…We were also successful in expanding the scope of this reaction towards the synthesis of chromanone/thiochromanone/pyanone/and thiopyranone fused N -acetylated pyridines. 38…”
Section: Synthesis Of Nitrogen-containing Heterocyclesmentioning
confidence: 99%
“…Ashitha et al (2017) reported a one-pot, multicomponent cascade annulation method for the synthesis of chromenopyridines using arylidenones, alkynes and nitriles, mediated by BF 3 .OEt 2 . [55] Reacting a mixture of (E)-3-benzylidenechroman-4one 1, aryl acetylene 51 and acetonitrile/benzonitrile/acrylonitrile 52 in presence of BF 3 .OEt 2 led to N-acyl substituted pyridine-fused chromans 53 in moderate to good yields (Scheme 18). Similarly, this reaction was also found to afford Nsubstituted chromeno-, thiochromeno-, pyrano-, and thiopyrano[3,4-c]pyridines too in high yields.…”
Section: Chromeno-[34-c]-pyridinesmentioning
confidence: 99%
“…Therefore, in continuation of our focused ongoing research interest in natural products and natural product based lead molecule identification for therapeutic applications, in the present work, we have isolated the major compound ( E )-Labda-8­(17),12-diene-15,16-dial. This was synthetically transformed to rationally designed triazole appended analogues and evaluated for their pancreatic lipase inhibitory potential.…”
mentioning
confidence: 94%